Chromosomal and morphometric characterization of Carollia perspicillata (Linnaeus 1758) in Colombian Caribbean region - Rumié Mendoza, Margarita (2018)
The Carollia genus is a diverse group of bats from the Neotropical region, the similarity of its morphometric characters and high level diversity make it difficult to pinpoint the exact identification of species from this genus along its distribution. However, despite the Carollia being common for Colombia, there does not exist some cytogenetic research for Colombian Caribbean region, therefore, it characterized its karyotype and cranial morphometry, providing useful data that can contribute to taxonomic identification of the genus. The specimens of C. perspicillata samples were collected in forest fragments and civil society reserves in the Córdoba department, Colombia. Captured 15 individuals (6 males and 9 females) obtaining average forearm values of 41.92 mm, tibia 18.49 mm and weight 16.80 g, in addition to the values obtained for the cranial, dental and mandibular measurements that confirm that the material was catalogued correctly as C. perspicillata. Five specimens were used for the karyotype analysis (3 males, 2 females), counting 262 metaphases. The diploid number of C. perspicillata was determined from 2n = 20/XX for females and 2n = 21XY1Y2 for males with Fundamental Number = 36. By band G, homogeneity was found in pairs 1, 2, 3 and 5. This research increases the geographic representativeness of the cytogenetic studies of C. perspicillata for the northern of Colombia, preserving normality in terms of the chromosomal number reported.